In silico Analysis of whole-Genome of Solanum lycopersicum for Alpha-Crystallin Domains Associated with Heat Stress Tolerance - Prakash, M K Chandra; Thomas, Reena Rosy; Mondal, Papiya (Journal of Horticultural Sciences, 2015)
Living organisms alter their gene-expression patterns to withstand stressful conditions. Drought, salinity, heat and chilling are potent abiotic stresses causing an alteration in gene expression. Among these, high temperature stress stimulates Heat Shock Transcription Factors (HSF) which activate heat shock promoters, thus turning on the heat shock genes. Heat shock proteins are, therefore, products of heat shock genes and are classified as per their molecular weight, including small heat shock proteins (sHsps). Hsps are chaperones playing an important role in stress tolerance. These consist of a conserved domain, flanked by N- and C-terminal regions termed the alphacrystallin domain (ACD), and are widely distributed in living beings. Their role as chaperones is to help the other proteins in protein-folding and prevent irreversible protein aggregation. The conserved domains in sHsps are essential for heat-stress tolerance and for their molecular chaperone activity, enabling plant survival under increasing temperatures, leading to adaptations needed for coping with extremes climatic conditions. The present study focusses on identification of ACDs in the whole-genome of Solanum lycopersicum. A multinational consortium, International Tomato Annotation Group (ITAG), funded in part by the EU-SOL Project, provides annotation of the whole genome of S. lycopersicumavailable in the public domain. We used several in silico methods for exploring alpha-crystallin domains in all the chromosomes of S. lycopersicum. Surprisingly, these ACDs were found to be present in all the chromosomes excepting Chromosome 4; these are highly conserved in sHsps and are related to heat tolerance.
Keywords: Solanum lycopersicum; Alpha-Crystallin Domain (ACD); Small Heat Shock Proteins (sHsps); in silico; Heat Stress